Pengaruh Assessment for Learning dalam Pembelajaran Kimia terhadap Hasil Belajar Siswa - Sufa Adatul Hasanah; Muchlis Muchlis (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to describe the effect of the implementation of assessment for learning (AfL) in chemistry learning on student learning outcomes. This type of research is pre-experiment. The design used in this research is One Group Pretest Posttest Design, with the same treatment in class XI, that is pretest - meeting 1 - posttest 1 - meeting 2 - posttest 2. Meetings 1 and 2 respectively are the implementation of AfL on the material of acidic buffer solutions and basic buffer solutions. The subjects of this research were students of class A and B SMAN 2 Bangkalan. Students' chemistry learning outcomes were obtained from the results of pretest, posttest 1, and posttest 2. Data analysis techniques using normality test followed by hypothesis testing and N-Gain test. The results showed that there was a significant difference between the pretest and posttest 1 and between posttest 1 and posttest 2 in classes A and B. Students' learning outcomes also improved based on the results of the N-Gain test. Based on the results of the research, it can be concluded that the implementation of AfL in learning chemistry has an effect on learning outcomes and is able to improve student learning outcomes